Investigating the anti-carcinogenic potential action of 1,2,3 triazole core compounds: impact of introducing an aldehyde or Nitro group, integrating cell line studies, and in silico ADME and protein target prediction - Huda Ghassan Hameed; Hayder B. Sahib; Zahraa Sabbar Omran (Pensoft Publishers, 2024)
The development of novel chemotherapeutic drugs begins with the suppression of cancer and angiogenesis. Ringed compounds with one or more heteroatoms are known as heterocyclic compounds. In organic chemistry and the pharmaceutical sector, heterocyclic compounds containing nitrogen atoms are valuable. In pharmaceutical chemistry, molecules containing a 1,2,3-triazole skeleton are particularly favored. They have great stability, making it simple to bind them to biomolecular targets. In this work, two 1,2,3-triazole scaffolds containing new chemical entities were assessed using the MTT assay against two malignant (MCF-7 and HCT116) and one normal (HUVECs) cell lines with the goal of creating a new leading prodrug for cancer treatment. The ligands were well characterized by FTIR and 1HNMR. In silico ADMET studies show acceptable pharmacokinetic properties. With the aid of the ligands' SWISS target protein prediction, the in silico binding to target proteins was examined. The two compounds exhibited a dose-dependent cytotoxic effect, with the H4 compound demonstrating a favorable selectivity index against MCF-7 breast cancer, indicating its potential as a leading compound for anticancer prodrugs.